PROFESSIONAL ORIENTATION THE FORMATION OF INFORMED CAREER CHOICES - Lohush, L. (Continuing Professional Education: Theory and Practice, 2019)
The article reveals the need to focus on youth vocational guidance, as part of vocational education. Choosing the profession must meet individual expectations and abilities of the individual. It vocational guidance aimed at achieving a balance between professional interests and abilities of man and society’s needs for specific types of professional activities. Therefore, vocational guidance of young people should be considered primarily from the standpoint of the social order of society, and prediction of future frames for the country. Professional orientation of young people is associated both with their own worldview and influence the environment as a conscious choice citizens profession creates conditions for obtaining the highest possible results from the work. The most professionally oriented youth should be considered preprofessional training. She directs them to form personal commitment to professional training in their chosen specialty, the formation of professionally significant qualities of professional interests, motivation, achievement in chosen field; facilitate adaptation to the process of higher education, the development of the capacity for professional self throughout professional.